Charging plasma microparticles by electron and ion fluxes with kappa distribution in collisional mode - Myrzaly М.; Masheyeva Р.У.; Jumagulov М.Н. (Recent Contributions to Physics, 2024)
This work investigates the current problem of charging dust particles in nonequilibrium plasma, taking into account the kappa distribution of particles. Equations are obtained to describe the charging of dust particles based on the kappa distribution, taking into account collisions of plasma particles leading to ion charging. The transition from a thin collisionless region li(e) << a in the environment of a dust grain to a wider region li(e) >> a is considered with the assumption that li(e) << lD and a << lD, where li(e) is the mean free path of the ion (electron), is the radius of the dust grains, and lD is the screening length. It is also assumed that ionization and recombination do not occur near a dust grain. An analytical model constructed with taking into account these assumptions is used to study the charging of dust particles in nonequilibrium plasma. Expressions for the fluxes of ions and electrons on the surface of dust particles are derived based on the kappa distribution and compared with the results of other authors obtained based on the Maxwellian distribution. Based on the balance of electron and ion fluxes, the charge of dust particles was obtained. The behavior of ion and electron densities in the vicinity of dust grains is briefly analyzed.